Does Sustainability Performance Constrain Earnings Management? The Role of Board Meeting Frequency - Vista Yulianti; Agus Fuadi; Ilfah Nur Azizah (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
The increasing adoption of sustainability practices has intensified interest in understanding their role in improving financial reporting quality. Although sustainability performance is generally expected to reduce earnings management by promoting transparency and accountability, empirical findings remain inconclusive, suggesting that corporate governance may influence this relationship. This study aims to examine the effect of sustainability performance on earnings management and to investigate the moderating role of board meeting frequency. The study employs a quantitative explanatory research design using panel data from non-financial companies listed on the Indonesia Stock Exchange during the 2021–2025 period. Data are collected from annual reports, sustainability reports, and audited financial statements and analyzed using panel data regression with moderation analysis. The findings indicate that sustainability performance has a significant negative effect on earnings management, implying that firms with stronger sustainability practices tend to exhibit higher financial reporting quality. Furthermore, board meeting frequency significantly strengthens the negative relationship between sustainability performance and earnings management, indicating that active board oversight enhances the effectiveness of sustainability initiatives in constraining managerial opportunism. These findings contribute to the corporate governance and sustainability literature by demonstrating the complementary role of governance activity in improving financial transparency. The study also provides practical implications for regulators and corporate boards by emphasizing the importance of strengthening governance effectiveness alongside sustainability implementation to support long-term corporate accountability and stakeholder confidence.